MRGPRX2 activation as a rapid, high-throughput mechanistic-based approach for detecting peptide-mediated human mast cell degranulation liabilities. Issue 1 (1st January 2020) - Lafleur, Marc A.; Werner, Jonathan; Fort, Madeline; Lobenhofer, Edward K.; Balazs, Mercedesz; Goyos, Ana
Abstract: Mast cells play key roles in allergy, anaphylaxis/anaphylactoid reactions, and defense against pathogens/toxins. These cells contain cytoplasmic granules with a wide spectrum of pleotropic mediators that are released upon activation. While mast cell degranulation (MCD) occurs upon clustering of the IgE receptor bound to IgE and antigen, MCD is also triggered through non-IgE-mediated mechanisms, one of which is via Mas-related G protein-coupled receptor X2 (MRGPRX2). MRGPRX2 can be activated by many basic biogenic amines and peptides. Consequently, MRGPRX2-mediated MCD is an important potential safety liability for peptide therapeutics. To facilitate peptide screening for this liability in early preclinical drug development, a rapid, high-throughput engineered CHO-K1 cell-based MRGPRX2 activation assay was evaluated and compared to histamine release in CD34 + stem cell-derived mature human mast cells as a reference assay, using 30 positive control and 29 negative control peptides for MCD. Both G protein-dependent (Ca 2+ endpoint) and -independent (β-arrestin endpoint) pathways were assessed in the MRGPRX2 activation assay. The MRGPRX2 activation assay had a sensitivity of 100% for both Ca 2+ and β-arrestin endpoints and a specificity of 93% (β-arrestin endpoint) and 83% (Ca 2+ endpoint) compared to histamine release in CD34 + stem cell-derived mature human mast cells. These findings suggest that assessing MRGPRX2 activation in an engineered cell model can provide value as a rapid, high-throughput, economical mechanism-based screening tool for early MCD hazard identification during preclinical safety evaluation of peptide-based therapeutics.